Embedding routine health checks for adults with intellectual disabilities in primary care: practice nurse perceptions. Issue 4 (9th February 2018) - Macdonald, S.; Morrison, J.; Melville, C. A.; Baltzer, M.; MacArthur, L.; Cooper, S. A.
Abstract: Background: Adults with intellectual disabilities (IDs) have consistently poorer health outcomes than the general population. There is evidence that routine health checks in primary care may improve outcomes. We conducted a randomised controlled trial of practice nurse led health checks. Here, we report findings from the nested qualitative study. Aim: To explore practice nurse perceptions and experience of delivering an anticipatory health check for adults with IDs. Design and Setting: Qualitative study in General Practices located in NHS Greater Glasgow and Clyde, Scotland, UK. Method: Eleven practice nurses from 11 intervention practices participated in a semi‐structured interview. Analysis was guided by a framework approach. Results: Practice nurses reported initially feeling 'swamped' and 'baffled' by the prospect of the intervention, but early misgivings were not realised. Health checks were incorporated into daily routines with relative ease, but this was largely contingent on existing patient engagement. The intervention was thought most successful with patients already well known to the practice. Chronic disease management models are commonly used by practice nurses and participants tailored health checks to existing practice. It emerged that few of the nurses utilised the breadth of the check instead modifying the check to respond to individual patients' needs. As such, already recognised 'problems' or issues dominated the health check process. Engaging with the health checks in this way appeared to increase the acceptability and feasibility of the check for nurses. There was universal support for the health check ethos, although some questioned whether all adults with IDs would access the health checks, and as a consequence, the long‐term benefits of checks. Conclusion: While the trial found the intervention to be dominant over standard health care, the adjustments nurses made may not have maximised potential benefits to patients. Increasing training could further improve the benefits that health checks provide for people with IDs.